5x+4+7x
To subtract 7x^3 - 5x^4, you first need to rearrange the terms in descending order of the exponents. So, the expression becomes -5x^4 - 7x^3. Since the terms have different exponents, you cannot directly subtract them. The result is simply -5x^4 - 7x^3.
5x-6+23-7x 5x-7x+23-6 (rearranged) -2x+17 (simplification).
To simplify the expression 18 + 7x - 12 + 5x, you first combine like terms. Combine the constants (18 and -12) to get 6. Then, combine the x terms (7x and 5x) to get 12x. Therefore, the simplified expression is 6 + 12x.
(4, -2)
65 = 2x - 7x 65 = -5x 65/-5 = -5x/-5 -13 = x
If it's + 7x, the answer is (2x + 3)(5x - 4) If it's - 7x, the answer is (2x - 3)(5x + 4)
7x-5x=8 2x=8 x=4
(21x3-23x2-76x-32)/(7x+4) = [3x2(7x4) -5x(7x+4)-8(7x+4)]/(7x+4)=3x2-5x-8
5x-7x = -2
7x=2x-4 5x=-4 x=-4/5
35x2-36x-32 = (5x-8)(7x+4) when factored. 35*-32 = -1120 = -56*20 since -56+20 = -36 (35x - 56)(35x + 20) divide by 7 and 5 the coefficients of the two binomials (5x - 8)(7x + 4) or 35x2 - 56x + 20x - 32 = 7x(5x - 8) + 4(5x - 8) = (5x - 8)(7x + 4)
7x = 5+5x 7x-5x = 5 2x = 5 x = 2.5
12x - 4 = 7x - 21 12x -7x = -21 + 4 5x = -17 x = -3.4
dsvcvWv
5x+4
-12x-2Given: -5x-(7x+2)This is the same as -5x-1(7x+2). Use the distributive property and multiply the -1 through (7x+2).-5x-7x-2Simplify.-12x-2
To subtract 7x^3 - 5x^4, you first need to rearrange the terms in descending order of the exponents. So, the expression becomes -5x^4 - 7x^3. Since the terms have different exponents, you cannot directly subtract them. The result is simply -5x^4 - 7x^3.